Effects of Various Hydrocolloids on Physical, Sensory and Total Quality of Lactic Acid Bacteria on Frozen Yogurt with Corn Oil as Fat Sources - Vinny Dwi Octavianti; Siti Susanti; Sri Mulyani (Journal of Applied Food Technology, 2021)
This study aims to determine the effect of various hydrocolloid on the quality of frozen yogurt with corn oil as its fat sources The ingredients used in this work were skim milk, corn oil, yogurt starter, arabian gum, carrageenan, gelatin, water and sugar. The different types of hydrocolloids T0 (0%), T1 (0.5% Arabian gum), T2 (0.5% carrageenan), T3 (0.5% gelatin) were used as stabilizer in order to characterize the pH, overrun, melting time, sensory test and total lactic acid bacteria of frozen yogurt product. pH of frozen yogurt was measured using a pH meter. Melting time was measured using a stopwatch, overrun was measured using beaker glass, sensory tests were done by panelists and total lactic acid bacteria was measured by Total Plate Count (TPC). Results show significant differences (P<0.05) on overrun, melting time, sensory test in frozen yogurt obtained using various types of hydrocolloids but show no significant differences (P>0.05) on pH dan total lactic acid bacteria. The best treatment was the addition of 0.5% gelatin because it has an optimal melting time, overrun and highest sensory test.